Palliative Senning in the Treatment of Congenital Heart Disease with Severe Pulmonary Hypertension - Penha,Juliano Gomes da (2015)
Background:Transposition of the great arteries (TGA) is the most common cyanotic cardiopathy, with an incidence ranging between 0.2 and 0.4 per 1000 live births. Many patients not treated in the first few months of life may progress with severe pulmonary vascular disease. Treatment of these patients may include palliative surgery to redirect the flow at the atrial level.Objective:Report our institutional experience with the palliative Senning procedure in children diagnosed with TGA and double outlet right ventricle with severe pulmonary vascular disease, and to evaluate the early and late clinical progression of the palliative Senning procedure.Methods:Retrospective study based on the evaluation of medical records in the period of 1991 to 2014. Only patients without an indication for definitive surgical treatment of the cardiopathy due to elevated pulmonary pressure were included.Results:After one year of follow-up there was a mean increase in arterial oxygen saturation from 62.1% to 92.5% and a mean decrease in hematocrit from 49.4% to 36.3%. Lung histological analysis was feasible in 16 patients. In 8 patients, pulmonary biopsy grades 3 and 4 were evidenced.Conclusion:The palliative Senning procedure improved arterial oxygen saturation, reduced polycythemia, and provided a better quality of life for patients with TGA with ventricular septal defect, severe pulmonary hypertension, and poor prognosis.